Data Hiding Application with Gokturk Alphabet Based Visual Cryptography Method - Tuncer, Turker; Avci, Engin (Gazi Univ, Fac Engineering Architecture, 2016)
Nowadays, a lot of secret sharing and visual cryptography (VC) based data hiding methods have been proposed. VC provides perfectly information security without using complex mathematical operations but VC methods generates noise-like data. Thus, this methods attract attention of attackers. To solve this problem, letter based VC methods are proposed. However, letter based VC methods are dependent on morphological features of letters. To solve this problem, a new letter based VC which used additive based secret sharing. The proposed letter based VC method is independent on morphological features of letters and this method can be used all of the letters. The proposed letter based VC method used letters of Gokturk in this paper. The secret data is divided into secret shares by using Gokturk Alphabet based VC and these secret shares are embedded into R, G and B layers of color images respectively. The experimental results show that the proposed VC based data hiding application is successfully.
Göktürk alfabesi tabanli görsel sir paylaşimi metodu ile veri gizleme uygulamasi
Keywords: Data hiding; letter based visual; cryptography; watermarking; information security; image processing